Non-apoptotic FAS signaling controls mTOR activation and extrafollicular maturation in human B cells - Staniek, Julian; Kalina, Tomas; Andrieux, Geoffroy; Boerries, Melanie; Janowska, Iga; Fuentes, Manuel; Díez, Paula; Bakardjieva, Marina; Stancikova, Jitka; Raabe, Jan; Neumann, Julika; Schwenk, Sabine; et al. (American Association for the Advancement of Science, 2024)
Fil: Staniek, Julian. Albert Ludwigs University of Freiburg; Alemania